Pengaruh Latihan Daya Ledak Otot Tungkai dan Latihan Kekuatan Otot Lengan Terhadap Peningkatan Kemampuan Shooting Free Throw pada Ekstrakulikuler Bola Basket SMA Negeri 1 Negara - I Made Ananda Krisna; I Ketut Addy Putra Indrawan; Marcus Chirtiawan Haemajudha (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to compare the effectiveness of leg muscle explosive power training and arm muscle strength training in improving free throw shooting ability in basketball extracurricular participants at State Senior High School 1 Negara. The study used a quantitative approach with an experimental method and a pretest-posttest two-group design. The study population consisted of 36 basketball extracurricular participants. The sample was selected using a purposive sampling technique and divided into two groups of 18 participants each through a matching technique (ordinal pairing). The first group received leg muscle explosive power training, while the second group received arm muscle strength training. Data were collected using a free throw shooting test before (pretest) and after (posttest) treatment, then analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, paired sample t-test, independent sample t-test, and the Mann-Whitney U test at a significance level of 0.05. The results showed that both types of training improved free throw shooting ability. However, there were differences in effectiveness between the two, so the type of training given affected the extent of the increase in participants' abilities. These findings indicate that selecting an appropriate training method is an important factor in optimizing free throw shooting abilities in extracurricular basketball participants.